EKSEKUSI JAMINAN FIDUSIA DI BANK SYARIAH MANDIRI KOTA MALANG DI TINJAU DARI FATWA DSN MUI NOMOR 68 TAHUN 2008 - Makruf, Solihan (Jurisdictie: Jurnal Hukum dan Syariah, 2014)
In the modern era bankings are not only collecting funds from the society and distributing them as loans. It is important for us to observe whether the activities are halal or not from Islamic perspective. Therefore, it is important to build dependable islamic bankings with high Islamic law awareness. The study has three research questions. They are: 1) How is the practice of fiduciary guarantee in Bank SyariahMandiri Kota Malang? 2) What is the perspective of National Sharia Board of MUI on fiduciary guarantee in Bank Syariah Mandiri Kota Malang? 3) How is the execution of fiduciary guarantee as the consequence of debtor’s failure in paying their debt in Bank Syariah Mandiri Malang?The study employs sociological or empirical law method. It is an approach to analyze an effectively established legislation or law.It analyzes qualitatively the implementation of fiduciary guarantee in Bank Syariah Mandiri Kota Malang. The dataconsists of primary data from interviews and secondary data from the library study. The writer uses descriptive analytical data analysis.Hasil penelitian menunjukan bahwa pelaksanaan jaminan dan eksekusi jaminan fidusia terhadap barang jaminan tidak sesuai dengan hukum yang ada dari perspektif hukum positif tentang jaminan fidusia dan dari perspektif hukum islam yang didasarkan pada fatwa Badan Syariah Nasional. Kesimpulannya, Bank Islam sering melakukan kesalahan pada prosedur eksekusi jaminan fidusia. Dari analisis tersebut, dapat disimpulkan bahwa prosedur jaminan fidusia dan eksekusinya di Bank Syariah Mandiri Kota Malang tidak sesuai dengan hukum yang ada. Seharusnya bank ini menerapkan prosedur sesuai dengan prinsip syariah dan fatwa Badan Syariah Nasional MUI, sebuah institusi yang menaungi bank-bank syariah dan hukum tentang jainan fidusia untuk memastikan pratik tersebut tidak akan merugikan pihak-pihak lain.